Measure for Measure - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1997)
"Measure for Measure" by William Shakespeare is a play written in 1603 or 1604. When Duke Vincentio leaves Vienna, he appoints the strict Angelo as his deputy. Angelo revives harsh laws and sentences young Claudio to death for fornication. When Claudio's sister Isabella, a novice nun, pleads for mercy, Angelo makes a shocking proposition: her virginity in exchange for her brother's life. Meanwhile, the Duke secretly remains in the city, disguised as a friar, observing the unfolding moral crisis and plotting to intervene. (This is an automatically generated summary.)
The First Folio, 1623
Wikipedia page about this book: https://en.wikipedia.org/wiki/Measure_for_Measure
Release date is 1997-12-01
Keywords: Comedy plays; Siblings -- Drama; Chastity -- Drama; Vienna (Austria) -- Drama